Riluzole-Rasagiline Hybrids: Toward the Development of Multi-Target-Directed Ligands for Amyotrophic Lateral Sclerosis - Albertini, Claudia; Salerno, Alessandra; Atzeni, Silvia; Uliassi, Elisa; Massenzio, Francesca; Maruca, Annalisa; Rocca, Roberta; Mecava, Marko; Silva, Filomena S G; Mena, Débora; Valente, Pedro; Duarte, Ana I; et al. (ACS chemical neuroscience, 2022)
Polypharmacology is a new trend in amyotrophic lateral sclerosis (ALS) therapy and an effective way of addressing a multifactorial etiology involving excitotoxicity, mitochondrial dysfunction, oxidative stress, and microglial activation. Inspired by a reported clinical trial, we converted a riluzole (1)-rasagiline (2) combination into single-molecule multi-target-directed ligands. By a ligand-based approach, the highly structurally integrated hybrids 3-8 were designed and synthesized. Through a target- and phenotypic-based screening pipeline, we identified hit compound 6. It showed monoamine oxidase A (MAO-A) inhibitory activity (IC50 = 6.9 μM) rationalized by in silico studies as well as in vitro brain permeability. By using neuronal and non-neuronal cell models, including ALS-patient-derived cells, we disclosed for 6 a neuroprotective/neuroinflammatory profile similar to that of the parent compounds and their combination. Furthermore, the unexpected MAO inhibitory activity of 1 (IC50 = 8.7 μM) might add a piece to the puzzle of its anti-ALS molecular profile.
Keywords: ALS; riluzole; MAO; lidé; MTDLs; benzothiazoles; Riluzole; amyotrofická laterální skleróza; Polypharmacology; Ligands; rasagiline; Neuroprotective Agents; Indans; riluzol; Amyotrophic Lateral Sclerosis; neuroprotektivní látky; indany; ligandy; Humans